The Role of International Migration Experience for Investment at Home: Direct, Indirect, and Equalising Effects in Senegal. Issue 6 (3rd April 2014) - Mezger Kveder, Cora; Beauchemin, Cris
Abstract This paper investigates the impact of international migration on investments of Senegalese in real estate and business assets in their home country, using longitudinal data from the 'Migration between Africa and Europe' survey. The objective is to examine the role of personal migration experience (direct role), access to migrant networks (indirect role), and migration as a compensation mechanism for disadvantaged groups (equalising role). The results suggest that personal migration experience stimulates investment in assets but that its role varies by the type of migration experience. Business owners are predominantly returnees who had migrated within Africa, while living or having lived in Europe increases the likelihood of investment in real estate. Moreover, migration helps overcome social disadvantages in access to asset ownership, at least for women and less educated individuals. In contrast, the investment behaviour of nonmigrants is not influenced by migration of family members or friends. Copyright © 2014 John Wiley & Sons, Ltd.